Private equity and venture capital in Europe : markets, techniques, and deals - Caselli, Stefano, 1969- (Academic Press, an imprint of Elsevier, 2018)
"Global financial markets might seem as if they increasingly resemble each other, but a lot of peculiar aspects qualify different markets with different levels of development. Private equity investors can take advantage of these variations. Structured to provide a taxonomy of the business, Private Equity and Venture Capital in Europe, Second Edition, introduces private equity and venture capital markets while presenting new information about the core of private equity: secondary markets, private debt, PPP within private equity, crowdfunding, venture philanthropy, impact investing, and more. Every chapter has been updated, and new data, cases, examples, sections, and chapters illuminate elements unique to the European model. With the help of new pedagogical materials, this Second Edition provides marketable insights about valuation and deal-making not available elsewhere. Covers new regulations and legal frameworks (in Europe and the US) described by data and tax rates Features overhauled and expanded pedagogical supplements to increase the versatility of the Second Edition Focuses on EuropeIncludes balanced presentations throughout the book"--